The role of umbilical artery doppler indices in predicting perinatal outcome in preeclampsia - Irowa, Omoregie; Hameed, Mohammad; Isaac, Nombur Lahaga; Elizabeth, Eti Arichi (International Journal of Research in Medical Sciences, 2023)
Background: Preeclampsia currently accounts for the majority of causes of perinatal morbidity and mortality. Umbilical artery Doppler (UAD) is a non-invasive effective method of antenatal fetal surveillance for early detection and prevention of potentially adverse perinatal outcome in preeclampsia. The objective of this study is to predict adverse perinatal outcome using UAD in Preeclampsia. Methods: This was a prospective cohort study in which 170 consecutively consenting women with preeclampsia were recruited. An UAD was done using Voluson P8 ultrasound. The pulsatility index, resistance index, systolic/diastole ratio. Reduced end diastolic flow, absent end diastolic flow and reversed end diastolic flow were measured. The participants were divided into two groups based on UAD indices findings. Both groups were followed up to determine their perinatal outcomes.The data was analyzed using SPSS version 20.0 for windows (IBM SPSS Inc, Chicago, IL, USA). Categorical variables were analyzed using Chi-Square ( 2) test and Fisher’s exact test p<0.05 was considered statistically significant. Specificity, sensitivity, PPV and NPV were determined. Results: The sensitivity, specificity, PPV, and NPV of umbilical artery Doppler in predicting adverse perinatal outcomes was 68.5%, 59.7%, 74.7%, and 52.1% respectively. Conclusions: Although the use of UAD indices in this study showed modest predictive values for adverse perinatal outcome in preeclampsia, it’s use should be combine with other methods of antenatal fetal surveillance to prevent adverse perinatal outcome.